Analisis Faktor-faktor Yang Mempengaruhui Cadangan Devisa Indonesia Bukti (Kointegrasi dan Kausalitas) - Hijri Juliansyah; Putri Moulida; Apridar Apridar (LPPM UNIMAL, 2020)
This study aims to analyze the factors that influence Indonesia's foreign exchange reserves by proving cointegration (long-run relationships) and causality (reciprocal relationships). The data used is time series data during the period January 2014-December 2018. The analytical method used in this study is cointegration test and granger causality with the approach of auto regressive lag (ARDL). The cointegration test results using the Bound test test indicated that between the variables of foreign exchange reserves, exports, the exchange rate, the BI Rate and inflation had a stability relationship of movements in the long run. While the results of the causality test showed that there is a one-way relationship between foreign exchange reserves and exports, and so there was a unidirectional relationship between foreign exchange reserves and the exchange rate and the same relationship between the BI Rate and foreign exchange reserves. Keywords: foreign exchange reserves, exports, exchange rates, BI Rate, inflation.